Determining drivers of phytoplankton carbon to chlorophyll ratio at Atlantic Basin scale - Smyth, Timothy; Moffat, David; Tarran, Glen; Sathyendranath, Shubha; Ribalet, Francois; Casey, John (Frontiers in Marine Science, 2023)
We demonstrate the ability of flow cytometry to determine species specific cellular carbon and chlorophyll content in vivo by using laboratory cultures of phytoplankton encompassing a wide range of cell sizes. When applied to the large Atlantic Meridional Transect flow cytometry dataset, we reveal patterns in the species-specific phytoplankton carbon (C), chlorophyll (Chl) and C:Chl ratio. For Prochlorococcus the range of C:Chl is between 2 – 604; for Synechococcus 0.5 – 558. Using a Random Forest machine learning approach, we show that predictability of phytoplankton C:Chl, dominated by the prevalence of Prochlorococcus, is largely driven by silicate and nitrite concentration in the Atlantic Ocean.